Comparison of the Conception Of Property Rights in Terms of Islamic Civil and Civil Law - Aip Piansah (Zona Law And Public Administration Indonesia, 2023)
Property rights are one part of human rights that have been regulated in the laws and regulations in Indonesia. Ownership can be owned by anyone who is entitled and valid according to written regulations. The focus of this discussion is to look for similarities and differences in the rules of the concept of property rights in terms of civil law (BW) and Islamic civil law (fiqh)). Property rights are regulated in the Third Chapter of Articles 570 – 624 of the Civil Code. Article 570 of the Civil Code explains that "Property rights are the right to enjoy a good more freely and to act on it completely freely, provided that it does not contradict the laws or general regulations established by the competent authority and provided that it does not interfere with the rights of others; All of these do not reduce the possibility of deprivation of rights in the public interest and appropriate compensation, based on statutory provisions In this case the author aims to examine the concept of property rights in terms of civil law and Islamic civil law in a normative juridical manner. This writing method uses an analytical description, describing the differences and similarities in property rights in civil law and Islamic civil law in a normative juridical manner. The results of this discussion look at the differences and similarities in the conception of property rights in terms of civil and Islamic civil law